2014
DOI: 10.3402/gha.v7.23121
|View full text |Cite
|
Sign up to set email alerts
|

Diet and nutritional status among children 24–59 months by seasons in a mountainous area of Northern Vietnam in 2012

Abstract: BackgroundSeasonal variation affects food availability. However, it is not clear if it affects dietary intake and nutritional status of children in Vietnam.ObjectivesThis paper aims at examining the seasonal variation in nutrition status and dietary intake of children aged 24–59 months.DesignA repeated cross-sectional study design was used to collect data of changes in nutritional status and diets of children from 24 to 59 months through four seasons in Chiem Hoa district, Tuyen Quang province, a predominately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…This situation could be due to seasonal food availability because this study had been conducted in rainy season and the previous one in dry season. It could also have an impact on malnutrition prevalence [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This situation could be due to seasonal food availability because this study had been conducted in rainy season and the previous one in dry season. It could also have an impact on malnutrition prevalence [8].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, instruction level could be implicated, while, in cocoa production zone, most people were never at school (56.4%), principally women [5]. So, they are not really aware of infant nutrition such as diversification stage [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that children in the capital city have a better nutritional status compared to other parts of the country. Stunted under five children in our study was much lower compared to other areas of the world like Ethiopia (57.5), [19] Philippines (34%), [16] North Vietnam (29.8%), [13] NW Ethiopia (24.9%), [12] and Thailand (19.9%). [20] This difference could be due to inclusion of children from the capital, Kathmandu and surrounding districts only.…”
mentioning
confidence: 95%
“…[5] A study in Thailand showed 8.3% obesity and another study in NW Ethiopia showed 35.5% overweight children under five. [12,20] A study done in Ilam, Nepal showed 17.5% overweight children in 2015. [18] This suggests that the problem of overweight and obesity is comparatively less in and around Kathmandu compared to other places of Nepal and different other countries.…”
mentioning
confidence: 99%